Optimiser les chances de réussite de l'étudiant à l'Université par l'acquisition de compétences transversales - Basco, Louis (Verbum – Analecta Neolatina, 2008)
The chances for a student to be successful during his university studies are determined by various factors. The cultural and socioeconomic heterogeneity of the university during the first year of studies calls for offering programmes which will assist students to build skills necessary to succeed at the university. An educational initiative centred around building a "student person" is possible.